Предмет: Алгебра,
автор: radkatronova
помогите пожалуйста )))
Приложения:
Ответы
Автор ответа:
0
(6x-12)²-36x²=0
(6x-12)²-(6x)²=0
Воспользуемся формулой a²-b²=(a-b)(a+b)
(6x-12-6x)(6x-12+6x)=0
-12 (12x-12)=0
12x=12
x=1
(6x-12)²-(6x)²=0
Воспользуемся формулой a²-b²=(a-b)(a+b)
(6x-12-6x)(6x-12+6x)=0
-12 (12x-12)=0
12x=12
x=1
Похожие вопросы
Предмет: Русский язык,
автор: qwerty646647
Предмет: Математика,
автор: bojebot
Предмет: Физика,
автор: uwuu0975gmailcom
Предмет: Алгебра,
автор: Nika205
Предмет: География,
автор: Liza11vol